Nano-catalyst sintered body for hydrogen production by methanol reforming, preparation method and application

CN118179518BActive Publication Date: 2026-10-09DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202211584844.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-10
Publication Date
2026-10-09
Estimated Expiration
2042-12-10

AI Technical Summary

Technical Problem

[0010]本发明旨在提供一种甲醇重整制氢用催化剂的制备方法,以克服现有催化剂在碱性水热条件下连续态甲醇重整制氢过程中选择性低、稳定性差的缺陷

Benefits of technology

[0026] The most significant difference between the preparation method of the sintered catalyst for methanol reforming to produce hydrogen provided by this invention and the prior art is that the catalyst contains only two metal species, copper and cerium. By controlling the copper and cerium content and the sintering temperature, a catalyst suitable for continuous methanol reforming to produce hydrogen under alkaline hydrothermal conditions can be obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118179518B_ABST
    Figure CN118179518B_ABST
Patent Text Reader

Abstract

The application provides a nano-catalyst sintered body for continuous methanol reforming hydrogen reaction under alkaline hydrothermal conditions, a preparation method of the catalyst sintered body and application of the catalyst sintered body. The catalyst sintered body is prepared from cheap and readily available copper source, cerium source and complexing agent through mixing, evaporation, calcination, molding and sintering. The catalyst sintered body does not contain alkali metal, alkaline earth metal, zinc, boron, aluminum, silicon and other elements which are easy to be lost due to the formation of soluble species under alkaline hydrothermal conditions, which can avoid the collapse of the catalyst during the reaction. The copper is used as the active species and the cerium is doped into the copper, so that the catalyst sintered body has high activity and high selectivity. By controlling the copper and cerium content and the sintering temperature, the obtained catalyst sintered body has good mechanical strength and structural stability without significant secondary growth of nano-particles. The catalyst provided by the application can meet the harsh requirements of the catalyst for continuous methanol reforming hydrogen reaction under alkaline hydrothermal conditions, and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of methanol reforming for hydrogen production, specifically relating to a sintered nanocatalyst for continuous methanol reforming for hydrogen production under alkaline hydrothermal conditions, a method for preparing the sintered catalyst, and applications of the sintered catalyst. Background Technology

[0002] Hydrogen is an important petrochemical feedstock and secondary energy source, obtainable through chemical reactions, water electrolysis, or microbial fermentation. Considering factors such as process, cost, and safety, the chemical reaction route is the preferred method for large-scale hydrogen production. The feedstocks for chemical hydrogen production are widely available, including fossil fuels, alcohols, and biomass. Among these, methanol offers advantages such as low price, high purity, mild reaction conditions, and ease of storage and transportation.

[0003] The most widely used methanol-to-hydrogen technology is methanol steam reforming. Its core is the reforming reaction of methanol with steam to produce hydrogen: CH3OH + H2O = 3H2 + CO2. Under the above reforming reaction conditions, methanol can also directly decompose to produce carbon monoxide, and can further undergo methanation to produce methane. Therefore, to obtain pure hydrogen, the methanol steam reforming products must be separated and purified. For example, in the methanol steam reforming hydrogen production methods disclosed in patent documents CN102145876A and CN108455526A, palladium membranes are used to separate the reforming products to obtain pure hydrogen. As another example, in the methanol steam reforming hydrogen production method disclosed in patent document CN1944239A, two pressure swing adsorption (PSA) devices are used to purify hydrogen, using a decarbonization adsorbent and a molecular sieve-based adsorbent, respectively. Furthermore, in the methanol steam reforming method for producing hydrogen disclosed in patent document CN107986232A, a methanation step is added on the basis of pressure swing adsorption to further reduce the carbon monoxide content in the resulting hydrogen.

[0004] Carbon dioxide is one of the products of methanol steam reforming for hydrogen production. If carbon dioxide can be removed from the reaction system through adsorption during the reaction, the methanol steam reforming for hydrogen production can be promoted in the forward direction, while inhibiting the formation of carbon monoxide and methane, thereby directly obtaining pure hydrogen in the reaction process. For example, patent document CN103274357A discloses an adsorption-enhanced method for methanol steam reforming to produce hydrogen. This method uses four parallel reactors and matching heating and depressurization equipment to achieve the above-mentioned adsorption-enhanced reaction process. The adsorbents used are magnesium aluminum hydrotalcite, activated carbon, molecular sieves, magnesium oxide, and alkali metal carbonates. In addition to being used for methanol steam reforming to produce hydrogen, the above-mentioned adsorption enhancement method has also been used in the steam reforming of other alcohols such as ethanol to produce hydrogen. Specific examples can be found in patent documents CN103752256A, CN103785344A, and CN110433811A.

[0005] In the methanol steam reforming hydrogen production reaction, both methanol and water react in the gaseous state. By increasing the reaction pressure, the phases of methanol and water can be changed from gaseous to liquid, thus achieving methanol hydrothermal reforming. During the hydrothermal reforming process, a water-soluble alkaline carbon dioxide absorbent can be further added to the liquid-phase reactants to achieve an absorption-enhanced methanol hydrothermal reforming hydrogen production reaction. For example, patent document CN101248004A discloses a continuous hydrogen production method based on the above principle, which uses alkaline electrolytes such as hydroxides, carbonates, and bicarbonates of lithium, sodium, potassium, rubidium, and cesium as carbon dioxide absorbents. The catalyst used in this process is a compound, complex, alloy, or mixture thereof of iron, cobalt, nickel, ruthenium, rhodium, palladium, iridium, and platinum. In addition, metallic catalyst promoters such as copper, zinc, and silver are added to the catalyst, as well as granular, powdered, coated extrusion matrix, and bulk carriers such as metals, metal oxides, silicon oxide, alumina, silicon oxide-alumina, zirconium oxide, titanium oxide, cerium oxide, carbon, silicon carbide, silicon nitride, and silicon boride. The suitable reaction temperature for the above continuous hydrogen production process is 200-250℃, and the reaction pressure is 1-10 MPa. Based on the same principle, patent document CN101857198A provides an example of absorption-enhanced continuous ethylene glycol liquid-phase reforming to produce high-purity hydrogen. The catalyst used in this method is a nickel-boehmite composite catalyst, and the alkaline carbon dioxide absorbent includes potassium hydroxide and sodium hydroxide.

[0006] Compared with methanol steam reforming hydrogen production technology, the continuous methanol reforming hydrogen production process under alkaline hydrothermal conditions has the following advantages: (1) The methanol hydrothermal reforming hydrogen production reaction enhanced by carbon dioxide absorption is more thermodynamically favorable and can be carried out at a lower reaction temperature than the methanol steam reforming hydrogen production reaction; (2) By adjusting the reaction conditions, high-purity hydrogen can be obtained. The hydrogen production system does not need to add a water-gas shift reactor for removing carbon monoxide or a pressure swing adsorption device for removing carbon dioxide, carbon monoxide, and methane. Therefore, the construction cost and operating energy consumption are lower than those of the methanol steam reforming hydrogen production process; (3) The reactor outlet pressure is high, and the number of compression stages required for the pressurization process of the obtained pure hydrogen is much less than that of the steam reforming hydrogen production process, which also helps to reduce construction costs and operating energy consumption; (4) The high system pressure also makes the device volume significantly smaller; (5) The continuous hydrogen production process used is highly efficient, simple in process, and easy to operate. Therefore, the successful development of a continuous methanol reforming process for hydrogen production under alkaline hydrothermal conditions will revolutionize existing methanol-to-hydrogen technology and promote the integration and efficient utilization of methanol and hydrogen, the two major "raw material-energy platforms".

[0007] Despite the numerous advantages of continuous methanol reforming for hydrogen production under alkaline hydrothermal conditions, its widespread application is currently limited by the performance of relevant catalysts. Specifically, the hydrogen production method disclosed in patent document CN101248004A uses compounds, complexes, alloys, or mixtures of iron, cobalt, nickel, ruthenium, rhodium, palladium, iridium, and platinum as catalysts. However, precious metals such as ruthenium, rhodium, palladium, iridium, and platinum are expensive and difficult to use on a large scale; while catalysts containing iron, cobalt, and nickel exhibit high methanation reactivity, resulting in high methane content in the products. The nickel-boehmite composite catalyst used in patent document CN101857198A also suffers from high methanation reactivity. Furthermore, catalyst supports well-known and commonly used in the field, such as silica and alumina used in patent document CN101248004A, are unstable in alkaline hydrothermal systems. Powders such as zirconium oxide, titanium oxide, cerium oxide, silicon carbide, silicon nitride, and silicon boride are not easily formed into molded bodies with high mechanical strength. Carbon material carriers, represented by activated carbon, are generally considered to be chemically inert. However, under alkaline conditions, carbon can even begin to react and generate hydrogen at around 100°C: C + 2NaOH + H2O = 2H2 + Na2CO3, which leads to catalyst breakdown (SAXENA S K. Hydrogen production by chemically reacting species[J]. International Journal of Hydrogen Energy, 2003, 28(1): 49-53). Furthermore, in the study of hydrogen production from cellulose via hydrothermal reforming, there have been reports of using Raney nickel as a catalyst (Wen G, Xu Y, Liu Q, Wang C, Liu H, Tian Z. Preparation of Ce-modified Raney Ni catalysts and their application in aqueous-phase reforming of cellulose[J]. Catalysis Letters, 2011, 141(12): 1851-1858). However, Raney catalysts typically contain about 10% aluminum to act as a binder. Under alkaline conditions, the Raney catalyst gradually disintegrates as aluminum is lost. These are all problems that need to be addressed in the current screening of catalysts for continuous methanol reforming to hydrogen production under alkaline hydrothermal conditions.

[0008] In methanol steam reforming catalysts, copper-based catalysts, represented by copper-zinc-aluminum oxides, have attracted much attention due to their high reactivity and few side reactions. Introducing rare earth elements such as lanthanum and cerium into these catalysts can further improve their performance (Sun Xiaoming, Sha Qihao, Wang Chenwei, Zhou Daojin. Research progress on copper-based catalysts for methanol reforming to produce hydrogen [J]. Journal of Chemical Industry and Engineering (China), 2021, 72(12): 5975-6001). For example, patent document CN101474563A discloses a methanol steam reforming catalyst formed by coating a cerium oxide-zirconia surface layer on the surface of a copper-zinc-aluminum oxide catalyst. The cerium oxide-zirconia surface layer helps stabilize the copper oxide on the catalyst surface, thereby accelerating the dissociation and adsorption of water and improving the activity and stability of the catalyst. Patent document CN113731429A discloses a methanol steam reforming catalyst containing copper oxide, zinc oxide, aluminum oxide, zirconium oxide, cerium oxide, and auxiliary agents magnesium oxide, lanthanum oxide, calcium oxide, and manganese oxide. The multi-component solid solution phase contained in this catalyst can promote the methanol dehydrogenation and carbon monoxide adsorption processes, thereby increasing the methanol conversion rate and reducing the carbon monoxide content in the reforming products. Patent document CN115025782A discloses a copper-based methanol steam reforming catalyst using nanorod-shaped cerium oxide as a support. This support facilitates the full exposure of copper active sites and the interfacial effect with copper, thus improving the catalyst's low-temperature activity. However, all three copper-based catalysts mentioned above are used in gas-solid phase catalytic systems. If applied to a continuous methanol reforming process for hydrogen production under alkaline hydrothermal conditions as described in patent document CN101248004A, the aforementioned problem of poor catalyst structural stability will still be encountered.

[0009] In conclusion, it is necessary to conduct further exploratory research on catalysts and their preparation methods suitable for continuous methanol reforming hydrogen production processes under alkaline hydrothermal conditions. Summary of the Invention

[0010] The present invention aims to provide a method for preparing a catalyst for methanol reforming to produce hydrogen, so as to overcome the defects of existing catalysts in continuous methanol reforming to produce hydrogen under alkaline hydrothermal conditions, such as low selectivity and poor stability.

[0011] To achieve this objective, the present invention provides a method for preparing a sintered nanocatalyst, the method comprising the following steps:

[0012] Step 1: Mix copper source, cerium source, complexing agent and water. The copper source is calculated as Cu, the cerium source is calculated as Ce, and the molar ratio of copper source to cerium source is 0.9-7.0, preferably 1.0-5.0, more preferably 1.2-3.5.

[0013] Step 2: Heat the mixture obtained in Step 1 to dryness;

[0014] Step 3: Calcine the dry adhesive obtained in Step 2 to obtain nano-catalyst powder. The calcination temperature is 300-800℃, preferably 400-750℃, more preferably 500-700℃, and the calcination time is 0.2-48h, preferably 2-24h, more preferably 4-12h.

[0015] Step 4: Shape the nano-catalyst powder obtained in Step 3;

[0016] Step 5: Sinter the nanocatalyst molded body obtained in Step 4 to obtain the nanocatalyst sintered body of the present invention. The sintering temperature is 700-1500℃, preferably 800-1300℃, more preferably 900-1100℃, and the sintering time is 1-24h, preferably 2-12h, more preferably 4-8h.

[0017] In the method for preparing the catalyst sintered body provided by the present invention, the copper source in step 1 is one or more of copper nitrate (II), copper formate (II), and copper acetate (II); the cerium source in step 1 is one or two of cerium nitrate (III) and cerium nitrate (IV) ammonium; and the complexing agent in step 1 is one or more of acetylacetone, formic acid, acetic acid, citric acid, tartaric acid, alginic acid, aminotriacetic acid, ethylenediaminetetraacetic acid, cyclohexanediaminetetraacetic acid, diethylenetriaminepentaacetic acid, glucose, and sucrose.

[0018] In the method for preparing the catalyst sintered body provided by the present invention, the mass of the complexing agent in step 1 is 10%-70% of the sum of the masses of the copper source, cerium source, and complexing agent, preferably 20%-55%, and more preferably 25%-40%.

[0019] To achieve the purpose of the invention, the present invention also provides a nanocatalyst sintered body obtained by the above-mentioned catalyst sintered body preparation method for continuous methanol reforming hydrogen production reaction under alkaline hydrothermal conditions.

[0020] To achieve the purpose of the invention, the present invention also provides an application of the above-mentioned catalyst sintered body in a continuous methanol reforming hydrogen production reaction under alkaline hydrothermal conditions. The reaction raw materials used in this process are liquid at room temperature and pressure, and contain water, methanol, and alkaline carbon dioxide absorbent. The reaction is carried out in a fixed-bed reactor, and under the reaction conditions, there is material that flows continuously in liquid form through the catalyst sintered body bed.

[0021] In the application of the catalyst sintered body provided by the present invention, the reaction conditions are as follows: reaction temperature of 150-320℃, preferably 180-290℃, more preferably 210-260℃; reaction pressure of 2-12MPa, preferably 4-10MPa, more preferably 5-8MPa; and reaction feed liquid hourly space velocity of 1-50h. -1 Preferred 5-30h -1 More preferably 10-20h -1.

[0022] In the application of the catalyst sintered body provided by the present invention, the alkaline carbon dioxide absorbent is one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.

[0023] In the application of the catalyst sintered body provided by the present invention, the mass fraction of methanol in the reaction raw materials is 1%-30%, preferably 5%-20%, more preferably 10%-15%, and the mass fraction of alkaline carbon dioxide absorbent is 5%-45%, preferably 10%-30%, more preferably 15%-20%.

[0024] In the application of the catalyst sintered body provided by the present invention, before the continuous methanol reforming hydrogen production reaction under alkaline hydrothermal conditions, the catalyst sintered body is activated in a reducing environment, and the reducing agent used is one or more of hydrogen, methane, carbon monoxide, and methanol.

[0025] In the application of the catalyst sintered body provided by the present invention, before the continuous methanol reforming hydrogen production reaction under alkaline hydrothermal conditions, the catalyst sintered body is activated in a water-containing reducing environment, and the reducing agent used is one or more of hydrogen, methane, carbon monoxide and methanol.

[0026] The most significant difference between the preparation method of the sintered catalyst for methanol reforming to produce hydrogen provided by this invention and the prior art is that the catalyst contains only two metal species, copper and cerium. By controlling the copper and cerium content and the sintering temperature, a catalyst suitable for continuous methanol reforming to produce hydrogen under alkaline hydrothermal conditions can be obtained.

[0027] The present invention offers the following advantages: The catalyst sintered body provided by this invention does not contain precious metals, but is prepared using readily available and inexpensive copper, cerium, and complexing agents as raw materials. This significantly improves the economic efficiency of the continuous methanol reforming hydrogen production process under alkaline hydrothermal conditions. The catalyst sintered body does not contain alkali metals, alkaline earth metals, zinc, boron, aluminum, silicon, or other elements that are easily lost under alkaline hydrothermal conditions due to the formation of soluble species. This prevents the catalyst sintered body from disintegrating during the reaction. Using copper as the active species and incorporating cerium gives the catalyst sintered body high activity and high selectivity. By controlling the copper and cerium content and the sintering temperature, the resulting catalyst sintered body achieves good mechanical strength and structural stability without significant secondary growth of nanoparticles. Therefore, the catalyst sintered body provided by this invention can meet the stringent requirements of the catalyst for the continuous methanol reforming hydrogen production reaction under alkaline hydrothermal conditions and has broad industrial application prospects. Attached Figure Description

[0028] Figure 1 This is the X-ray powder diffraction pattern of the sintered nanocatalyst obtained in Example 1.

[0029] Figure 2 The image shows the X-ray powder diffraction pattern of the activated carbon-supported copper oxide catalyst obtained in Comparative Example 1.

[0030] Figure 3 This is the X-ray powder diffraction pattern of the copper-zinc-aluminum oxide catalyst obtained in Comparative Example 2. Detailed Implementation

[0031] The following embodiments will further illustrate the present invention. However, the present invention is not limited to the following embodiments.

[0032] Example 1

[0033] Catalyst preparation: 12.1 g of copper nitrate (II) (Cu(NO3)2·3H2O), 22.3 g of cerium nitrate (III) (Ce(NO3)3·6H2O), 31.7 g of citric acid, and 100.1 g of water were added to a 1 L glass beaker and stirred until the reactants were completely dissolved. The Cu / Ce molar ratio in the resulting solution was 1.0, and the mass of citric acid was 48% of the sum of the masses of copper nitrate (II), cerium nitrate (III), and citric acid. The solution was heated to dryness, and the resulting dry gel was calcined at 450℃ for 0.5 h to obtain nano-catalyst powder. The nano-catalyst powder was pressed, crushed, and sieved to obtain shaped bodies with a particle size of 20-40 mesh. The shaped bodies were placed in a muffle furnace and sintered at 1000℃ for 4 h to obtain the sintered nano-catalyst body. The X-ray powder diffraction pattern of the obtained sintered catalyst body is shown below. Figure 1 As shown in the figure. X-ray powder diffraction analysis results show that the catalyst sintered body contains two crystalline phases: CuO (PDF#00-045-0937) and CeO2 (PDF#01-081-0792). The crystallite sizes corresponding to each diffraction peak calculated according to the Scherrer formula are listed in the table below.

[0034]

[0035]

[0036] Methanol reforming for hydrogen production: 6.6 g of the above-mentioned sintered nanocatalyst (3.0 mL in volume) was placed in the isothermal section of a stainless steel microreactor, with stainless steel beads filling both ends of the catalyst. The reactor was sealed, the air inside was replaced with high-purity nitrogen and leak tested, then high-purity hydrogen was introduced, and the reactor was activated at 0.1 MPa and 248 °C for 1 h. The gas inside the reactor was replaced again with high-purity nitrogen to carry out the methanol reforming for hydrogen production reaction. The reactants consisted of 10% methanol, 22% potassium carbonate, and the remainder water. The reaction conditions were: reaction temperature 257 °C, reaction pressure 7.4 MPa, and liquid hourly space velocity (LISH) of the reactants 10.3 h⁻¹. -1Under the above reaction conditions, the hydrogen production rate of this catalyst was 12.3 mL. 氢 ·mL 催化剂 -1 ·min -1 The hydrogen purity is 99.906%, and the contents of methane, carbon monoxide, and carbon dioxide are 46 ppm, 22 ppm, and 869 ppm, respectively.

[0037] Example 2

[0038] Catalyst preparation: 19.9 g of copper(II) acetate (Cu(CH3COO)2·H2O), 26.3 g of cerium(IV) ammonium nitrate ((NH4)2Ce(NO3)6), 20.1 g of acetylacetone, and 300.1 g of water were added to a 1 L glass beaker. The mixture was heated and stirred until the reactants were completely dissolved. The Cu / Ce molar ratio in the resulting solution was 2.1, and the mass of acetylacetone was 30% of the sum of the masses of copper(II) acetate, cerium(IV) ammonium nitrate, and acetylacetone. The solution was heated to dryness, and the resulting dry gel was calcined at 600℃ for 1 h to obtain nanocatalyst powder. The nanocatalyst powder was pressed, crushed, and sieved to obtain shaped bodies with a particle size of 20-40 mesh. The shaped bodies were placed in a muffle furnace and sintered at 1200℃ for 2 h to obtain the sintered nanocatalyst body.

[0039] Methanol reforming for hydrogen production: 6.4 g of the above-mentioned sintered nanocatalyst (2.5 mL in volume) was placed in the isothermal section of a stainless steel microreactor, with stainless steel beads filling both ends of the catalyst. The reactor was sealed, and after purging the air with high-purity nitrogen and testing for leaks, a methanol-water solution (64% methanol by mass) was introduced and activated at 6.0 MPa and 261 °C for 6 h. The gas in the reactor was then purged again with high-purity nitrogen to carry out the methanol reforming for hydrogen production reaction. The reactants consisted of 8% methanol, 13% sodium hydroxide, and the remainder water. The reaction conditions were: reaction temperature 247 °C, reaction pressure 5.1 MPa, and liquid hourly space velocity (LISH) of the reactants 11.2 h⁻¹. -1 Under the above reaction conditions, the hydrogen production rate of this catalyst was 19.5 mL. 氢 ·mL 催化剂 -1 ·min -1 The hydrogen purity is 99.910%, and the contents of methane, carbon monoxide, and carbon dioxide are 762 ppm, 96 ppm, and 41 ppm, respectively.

[0040] Example 3

[0041] Catalyst preparation: 45.4 g of copper formate (II) (Cu(HCO2)2·4H2O), 21.7 g of cerium nitrate (III) (Ce(NO3)3·6H2O), 12.0 g of alginic acid, and 336.3 g of water were added to a 1 L glass beaker. The mixture was heated and stirred until a viscous gel formed. The Cu / Ce molar ratio in the resulting gel was 4.0, and the mass of alginic acid was 15% of the sum of the masses of copper formate (II), cerium nitrate (III), and alginic acid. The gel was heated to dryness, and the resulting dry gel was calcined at 750℃ for 3 h to obtain nano-catalyst powder. The nano-catalyst powder was pressed, crushed, and sieved to obtain shaped bodies with a particle size of 20-40 mesh. The shaped bodies were placed in a muffle furnace and sintered at 1050℃ for 0.5 h to obtain the sintered nano-catalyst body.

[0042] Methanol reforming for hydrogen production: 6.1 g of the above-mentioned sintered nanocatalyst (3.4 mL in volume) was placed in the isothermal section of a stainless steel microreactor, with stainless steel beads filling both ends of the catalyst. The reactor was sealed, the air inside was replaced with high-purity nitrogen, and leaks were checked. Methanol was then introduced, and the reactor was activated at 1.5 MPa and 350 °C for 8 h. The gas inside the reactor was again replaced with high-purity nitrogen to carry out the methanol reforming for hydrogen production reaction. The reactants consisted of 21% methanol, 41% potassium hydroxide, and the remainder water. The reaction conditions were: reaction temperature 271 °C, reaction pressure 9 MPa, and liquid hourly space velocity (LISH) of the reactants 15.0 h⁻¹. -1 Under the above reaction conditions, the hydrogen production rate of this catalyst was 16.8 mL. 氢 ·mL 催化剂 -1 ·min -1 The hydrogen purity is 99.930%, and the contents of methane, carbon monoxide, and carbon dioxide are 281 ppm, 10 ppm, and 407 ppm, respectively.

[0043] Example 4

[0044] Catalyst preparation: The unsintered shaped body obtained in Example 1 was placed in a muffle furnace and sintered at 850°C for 2 hours. The sintered nanocatalyst body was then obtained.

[0045] Methanol reforming for hydrogen production: 6.9 g of the above-mentioned sintered nanocatalyst (3.7 mL in volume) was placed in the isothermal section of a stainless steel microreactor, with stainless steel beads filling both ends of the catalyst. The reactor was sealed, the air inside was replaced with high-purity nitrogen, and after leak testing, carbon monoxide was introduced, and the reactor was activated at 0.2 MPa and 310 °C for 3 h. The gas inside the reactor was again replaced with high-purity nitrogen to carry out the methanol reforming for hydrogen production reaction. The reactants consisted of 2% methanol, 12% sodium carbonate, and the remainder water. The reaction conditions were: reaction temperature 245 °C, reaction pressure 4.4 MPa, and liquid hourly space velocity (LISH) of the reactants 3.9 h⁻¹. -1 Under the above reaction conditions, the hydrogen production rate of this catalyst is 2.7 mL. 氢 ·mL 催化剂 -1 ·min -1 The hydrogen purity is 99.827%, and the contents of methane, carbon monoxide, and carbon dioxide are 873 ppm, 135 ppm, and 717 ppm, respectively.

[0046] Compare with Example 1

[0047] Catalyst preparation: Copper oxide catalysts supported on activated carbon were prepared using an impregnation method. The X-ray powder diffraction pattern of the obtained catalyst is shown below. Figure 2 As shown. X-ray powder diffraction analysis results indicate that the copper oxide in the catalyst exhibits two crystalline phases: CuO (PDF#00-045-0937) and Cu2O (PDF#03-065-3288). Based on the Scherrer equation, the crystallite size of CuO is calculated to be 23 nm ((002) peak), and the crystallite size of Cu2O is 34 nm ((111) peak). Wavelength dispersive X-ray fluorescence spectroscopy analysis results indicate that the mass fraction of copper in the catalyst is 17%.

[0048] Methanol reforming for hydrogen production: 1.8 g of the above-mentioned activated carbon-supported copper oxide catalyst (3.1 mL in volume) was used in a continuous methanol reforming reaction for hydrogen production under alkaline hydrothermal conditions. The activation and reaction conditions were the same as in Example 1. The catalyst was inactive. Upon removal of the spent catalyst from the reactor, it was found that the activated carbon particles were partially pulverized.

[0049] Compare with Example 2

[0050] Catalyst Preparation: A copper-zinc-aluminum oxide catalyst with a copper, zinc, and aluminum atomic ratio of 2:2:1 was prepared using a co-precipitation method. The catalyst was then tableted, crushed, and sieved to obtain a shaped catalyst with a particle size of 20-40 mesh. The X-ray powder diffraction pattern of the obtained catalyst is shown below. Figure 3 As shown.

[0051] Methanol reforming for hydrogen production: 3.4 g of the aforementioned copper-zinc-aluminum oxide catalyst (3.0 mL) was used in a continuous methanol reforming reaction under alkaline hydrothermal conditions. The activation and reaction conditions were the same as in Example 2. During the activation stage, a large amount of gas was observed to be generated. Chromatographic analysis showed that the generated gas consisted of hydrogen, carbon dioxide, and small amounts of carbon monoxide and methane. After the reaction began, a large amount of gas was observed to be generated. Subsequently, the bed pressure gradually increased, and the gas production gradually decreased. The reaction was immediately stopped. Upon disassembling the reactor, it was found that the catalyst had completely disintegrated and clogged the bed. White flocculent material was discharged with the liquid products.

[0052] Compare with Example 3

[0053] Catalyst preparation: 9.9 g of copper nitrate (II) (Cu(NO3)2·3H2O), 22.3 g of cerium nitrate (III) (Ce(NO3)3·6H2O), 31.7 g of citric acid, and 100.1 g of water were added to a 1 L glass beaker and stirred until the reactants were completely dissolved. The Cu / Ce molar ratio in the resulting solution was 0.8, and the mass of citric acid was 50% of the sum of the masses of copper nitrate (II), cerium nitrate (III), and citric acid. The solution was heated to dryness, and the resulting dry gel was calcined at 450℃ for 0.5 h to obtain nano-catalyst powder. The obtained nano-catalyst powder, when pressed into tablets, easily crumbles into powder upon contact, making it unsuitable for granulation, sintering, or use in reactions.

[0054] Compare with Example 4

[0055] Catalyst preparation: The unsintered shaped body obtained in Example 3 was placed in a muffle furnace and sintered at 550°C for 6 hours. The resulting sintered catalyst body was easily crushed by hand and could not be used in the reaction.

[0056] The results of the above examples and comparative examples show that catalysts supported on activated carbon and catalysts containing zinc and aluminum will disintegrate under alkaline hydrothermal conditions, and therefore are not suitable for continuous methanol reforming to hydrogen production under alkaline hydrothermal conditions. Using copper as the active species and incorporating cerium is one of the reasons why the catalyst provided by this invention exhibits high activity and high selectivity. At the same time, the copper and cerium content of the catalyst and the sintering temperature also significantly affect the catalytic performance and structural stability of the resulting catalyst body.

Claims

1. A method for preparing a sintered nanocatalyst for continuous methanol reforming to produce hydrogen under alkaline hydrothermal conditions, characterized in that, The sintered nanocatalyst body is prepared by a method comprising the following steps: Step 1: Mix the copper source, cerium source, complexing agent, and water. The copper source is calculated as Cu, and the cerium source is calculated as Ce. The molar ratio of the copper source to the cerium source is 0.9–7.

0. Step 2: Heat the mixture obtained in Step 1 to dryness. Step 3: Calcining the dry adhesive obtained in Step 2 to obtain nano-catalyst powder. The calcination temperature is 300-800℃, and the calcination time is 0.2-48h. Step 4: Shape the nano-catalyst powder obtained in Step 3. Step 5: Sinter the nanocatalyst molded body obtained in Step 4 to obtain the sintered nanocatalyst body. The sintering temperature is 700-1500℃ and the sintering time is 1-24h.

2. The preparation method according to claim 1, characterized in that: Step 1: Mix the copper source, cerium source, complexing agent, and water. The copper source is calculated as Cu, and the cerium source is calculated as Ce. The molar ratio of the copper source to the cerium source is 1.0–5.

0. Step 3: Calcining the dry adhesive obtained in Step 2 to obtain nano-catalyst powder. The calcination temperature is 400-750℃, and the calcination time is 2-24 hours. Step 5: Sinter the nanocatalyst molded body obtained in Step 4 to obtain the sintered nanocatalyst body. The sintering temperature is 800-1300℃ and the sintering time is 2-12h.

3. The preparation method according to claim 1, characterized in that: The copper source mentioned in step 1 is one or more of copper nitrate (II), copper formate (II), and copper acetate (II); The cerium source mentioned in step 1 is one or two of cerium(III) nitrate and cerium(IV) ammonium nitrate; The complexing agent mentioned in step 1 is one or more of the following: acetylacetone, formic acid, acetic acid, citric acid, tartaric acid, alginic acid, nitric acid, ethylenediaminetetraacetic acid, cyclohexanediaminetetraacetic acid, diethylenetriaminepentaacetic acid, glucose, and sucrose.

4. The preparation method according to claim 1 or 3, characterized in that, The mass of the complexing agent mentioned in step 1 is 10%-70% of the sum of the masses of the copper source, cerium source, and complexing agent.

5. The preparation method according to claim 4, characterized in that, The mass of the complexing agent mentioned in step 1 is 20%-55% of the sum of the masses of the copper source, cerium source, and complexing agent.

6. The application of a sintered nanocatalyst prepared by the method of claim 1 in a continuous methanol reforming hydrogen production reaction under alkaline hydrothermal conditions, characterized in that... The reaction feedstock is in a liquid state at room temperature and pressure, containing water, methanol, and alkaline carbon dioxide absorbent. The reaction is carried out in a fixed-bed reactor, where, under the reaction conditions, there is material that flows continuously in liquid form through the catalyst bed.

7. The application according to claim 6, characterized in that, The reaction conditions are as follows: reaction temperature 150-320℃, reaction pressure 2-12MPa, and liquid hourly space velocity of the reaction feedstock 1-50h⁻¹. -1 .

8. The application according to claim 6, characterized in that, The reaction conditions are as follows: reaction temperature 180-290℃, reaction pressure 4-10MPa, and reaction liquid hourly space velocity 5-30h. -1 .

9. The application according to claim 6, characterized in that, The alkaline carbon dioxide absorbent is one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.

10. The application according to claim 6, characterized in that, The mass fraction of methanol in the reaction raw materials is 1%-30%, and the mass fraction of alkaline carbon dioxide absorbent is 5%-45%.

11. The application according to claim 6, characterized in that, The mass fraction of methanol in the reaction raw materials is 5%-20%, and the mass fraction of alkaline carbon dioxide absorbent is 10%-30%.

12. The application according to claim 6, characterized in that, Before carrying out a continuous methanol reforming reaction to produce hydrogen under alkaline hydrothermal conditions, the catalyst is activated in a water-containing reducing environment. The reducing agent used is one or more of hydrogen, methane, carbon monoxide, and methanol.

Citation Information

Patent Citations

  • Hydrogen production using electrochemical reforming and electrolyte regeneration

    CN101248004A

  • Preparation method of catalyst for hydrogen production from methanol-steam reforming

    CN101474563A

  • One-step method for continuously preparing high-purity hydrogen through ethylene glycol aqueous-phase reforming

    CN101857198A

  • Method for producing hydrogen by reforming methanol steam

    CN102145876A

  • Methanol steam reforming hydrogen production method and device based on adsorption reinforcement

    CN103274357A